Production and reproduction responses for dairy cattle supplemented with oral calcium bolus after calving: Systematic review and meta-analysis - Ainhoa Valldecabres; Rúbia Branco-Lopes; Christian Bernal-Córdoba; Noelia Silva-del-Río (JDS Communications, 2023)
Among the commonly implemented strategies developed to support calcium (Ca) metabolism postpartum, oral Ca supplementation is within the most studied. However, research shows varying responses to treatment in regard to production and reproduction. Our objectives were (1) to identify and synthesize the literature evaluating the associations between postpartum oral Ca supplementation as bolus and milk yield and risk of pregnancy to first service using a systematic review, and (2) to quantify these associations using meta-analytical methods. Nine relevant studies published between January 2010 and September 2021 were identified after systematic search of 4 databases (Biosis, CAB Abstracts, Medline, Scopus). The studies were conducted in commercial confined and grazing farms. Eight of the 9 studies reported feeding low to negative dietary cation-anion difference diets prepartum. Oral Ca bolus supplementation strategies varied among studies but were predominantly centered on the first 24 h postpartum. Milk yield and pregnancy to first service were evaluated in 9 and 6 of the studies, respectively. Other productive (energy-corrected milk yield, peak milk yield, or fat and protein concentrations) and reproductive (estrus cyclicity, days from calving to first service, or pregnancy by 150 or 210 days in milk) outcomes were evaluated in 4 of the studies. The meta-analyses revealed a lack of evidence for associations between prophylactic blanket postpartum oral Ca bolus supplementation and milk yield (including 8 studies) or risk of pregnancy to first service (including 6 studies). Some of the evaluated studies reported statistically significant associations after data stratification. However, not enough studies reported estimates for the evaluated conditional factors to perform a meta-analysis among the identified subgroups. In conclusion, future research should study and report the production, reproduction, and health estimates of cow-level conditional factors of interest for the evaluated response, and investigate alternative regimes of oral Ca bolus supplementation.